Measurement of three-dimensional orientation of golf club head with one camera - Wataru KIMIZUKA (The Japan Society of Mechanical Engineers, 2016)
Golfers' swings vary with each individual and golf club manufacturers provide the service called “Fitting”, to select an appropriate golf club for each swing, to an each golfer. In order to find the appropriate golf club for each golfer, it is necessary to measure the position and orientation of a golf club head. It can be supposed that the measurement error needs to be less than 0.5 degree. There is an existing method whereby the three-dimensional (3D) orientation of a golf club head is measured from the 3D positions of points on the golf club head. This method is generally used in the area of motion analysis, and has problems in that the system has many restrictions in its installation, large installation space is required, and costs are incurred to the future expansion of the fitting service to many locations, as two or more cameras are needed. The “Fitting” service requires a method that needs small space, low cost and little calculation time. Therefore, A method was developed, whereby the 3D orientation of a golf club head was calculated based on one image from just one camera using the Newton-Raphson method, which needs little calculation time, and the measurement accuracy was validated compared with the experimental results. It was proved that the developed method is useful to a golf club fitting service because the measurement error is less than 0.5 degree of our target even when various golfers' swings are measured, whereby markers are attached possibly near the outline of the head in the case of the farthest distance between markers from 80 to 95 mm, and then the coordinates of the marker center are identified by calculation from luminance and coordinates of each pixel in an area surrounding the marker.